2017
DOI: 10.2147/ceg.s135346
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in inflammatory bowel disease: results of a prospective controlled cohort study in Germany (NET<sub>IBD</sub>)

Abstract: Background/aimsPatients with inflammatory bowel disease (IBD) need comprehensive, interdisciplinary and cross-sectoral health care. In Germany, evidence-based care pathways have been developed to improve the quality of care of IBD patients. We aimed to evaluate the effects of the implementation of some of these recommendations on patient-related outcomes.MethodsIn a region of North Germany, outpatients with IBD were recruited by gastroenterologists (intervention group). Three activities based on the recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
10
0
5
Order By: Relevance
“…[ 24 , 30 , 31 ] In this study, we observed that patients with CD received more immunomodulator and biologic therapy than patients with UC, suggesting the fact that patients with CD were more difficult to treat with conventional therapy. [ 4 , 19 ] A low rate of steroid usage among our patients with IBD, similar to the Western reports, [ 30 , 32 , 33 ] may reflect the improved quality of IBD care in Taiwan in the past one decade. [ 2 , 8 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 30 , 31 ] In this study, we observed that patients with CD received more immunomodulator and biologic therapy than patients with UC, suggesting the fact that patients with CD were more difficult to treat with conventional therapy. [ 4 , 19 ] A low rate of steroid usage among our patients with IBD, similar to the Western reports, [ 30 , 32 , 33 ] may reflect the improved quality of IBD care in Taiwan in the past one decade. [ 2 , 8 , 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Drei Viertel der Teilnehmer/innen der IG gaben an, dass ihnen die 3 Bewegungstagebücher geholfen hätten, ihre Vorsätze im Alltag dauerhaft umzusetzen. Die Teilnehmer, die dies verneinten, berichteten überwiegend, dass sie im Alltag untergingen oder dass sie [19,20].…”
Section: Zufriedenheit Mit Dem Nachsorgekonzeptunclassified
“…In 2013, our working group started 2 longitudinal studies, REHA IBD [22] and NET IBD [21], with comparable measuring instruments and parallel time points of measurement. For evaluating the efficacy of various interventions on the course of disease, in REHA IBD , adult rehabilitants in a specialist rehabilitation clinic with CD or UC as first diagnosis, and in NET IBD , CD and UC patients treated in 28 gastroenterological specialist practices as well as 2 IBD outpatient clinics, were recruited consecutively and prospectively.…”
Section: Data Sourcesmentioning
confidence: 99%
“…For this purpose, data from 2 recent research studies on health services were reanalyzed. In both, disease activity was recorded both with the GIBDI (embedded in a patient questionnaire) and with the physician-documented activity indices pMS (in the case of UC) and HBI (in the case of CD) [21,22].…”
Section: Introductionmentioning
confidence: 99%